ANALISIS PERMASALAHAN KESULITAN MEMBACA PADA SISWA KELAS IV SD PELANGI MEDAN TEMBUNG - Silalahi, Jernita Damayanti; Sinaga, Fajar Riska; Puri Kesuma, Keysha Argadia; Nur, Khairiah; Sihombing, Firtswin; Anhar, Muh (Universitas Negeri Medan, 2024)
The purpose of this study was to determine the reasons behind the reading difficulties experienced by elementary school students, as well as the effects of implementing tutoring and tutoring. This type of research combines elements of descriptive and qualitative research. Data triangulation is the process of collecting data through documentation, interview, and observation techniques. Techniques for data analysis include data reduction, data visualization, and conclusion or verification. The findings of this study show that students' reading difficulties due to internal and external factors, such as students' lack of ability to mix words, their inability to distinguish almost identical letters, and their inability to combine sentences, can affect their reading comprehension. Teachers can propose that students read for fifteen minutes during class and work with their parents as a solution. Keywords: Causes, Reading Difficulty, Elementary School Children